Mechanical properties and durability performance of concretes with Limestone Calcined Clay Cement (LC3). (May 2018) - Dhandapani, Yuvaraj; Sakthivel, T.; Santhanam, Manu; Gettu, Ravindra; Pillai, Radhakrishna G.
Abstract: The adoption of any binder system for structural concrete depends on the performance characteristics desired for addressing the long-term deformation and durability concerns. The major properties influencing the performance includes the shrinkage characteristics governing the long-term deformation, and durability characteristics related to various transport mechanisms, governing the performance in different service conditions. This paper describes the potential of Limestone Calcined Clay Cement (LC 3 ) for use in structural concrete in comparison with Ordinary Portland Cement (OPC) and fly ash based blended cement (FA30). Three types of concrete mixtures were designed for the study, two based on achieving an equivalent strength grade (M30 and M50 concrete grade) with each binder, and the third with equal binder content and w/b ratio. Mechanical properties such as compressive strength and elastic modulus, and autogenous and drying shrinkage, along with various durability parameters of the different concretes were assessed. Oxygen permeability, rapid chloride penetration, chloride migration, resistivity development and water sorptivity were the various parameters considered for evaluation of durability performance. The results indicate the superiority of LC 3 binder over other binders in producing durable concrete, especially in a chloride laden environment. The major reason for the better performance was attributed to the more compact and dense microstructure of the system with the LC 3 binder against OPC and FA30. The drying shrinkage performance was seen to be similar for concrete with all three binders.